Education and science: current trends - Bodrov A. G., Nikishina A. A., Novikov I. A., Novikov A. P., Surkova G. V., Petrova D. D., Samostroenko G. M., Shatokhina O. V., Cherkashin I. S., Kapustina N. V., Rustamova I. T., Savenkov D. L., Veselova N. I., Grigorian S. S., Milioshina N. A., Firsova I. A., Chibilyova V. P., Chibiliov A. A., Sagitova V. R., Borovkova V. A., Borovkova V. A., Shevtsov V. V., Efremov A. Y., Diakieva B. B., Averianova E. V., Belonovskaia I. D., Sorokina O. A., Rakhimova O. N., Emelianova E. V., Chereshneva I. E., Kokhanova L. A., Golovko S. B., Khokhrina I. S., Khachev M. M., Temmoeva S. A., Cherkasova O. A., Zakirov R. S., Belousova rimma iurevna R. I., Novoselova A. N., Podoplelova N. M., Danilchenko S. L., Boldyrikhina V. N. (Education and science: current trends, 2018)
theoretical foundations and principles of project training for students in the specialty «Journalism», as a way to motivate a journalist for the profession is studied by the authors. The concept of project training for journalists is based on the idea that training should be motivating, especially when it comes to specialized discipline. The result of such training should be considered the skills and abilities generated by students to use the new things that they received in the course of their studies. The authors summarizing their own experience and the practice of colleagues, determine the main characteristics of this method and the principles, following which allows to obtain the desired results. The definition of «project training» is given as an organization of the educational process, when the study of a course or the entire cycle of courses in a specialty is aimed at the final result obtained in the process of setting the task and its implementation. Mechanisms to achieve this goal are training, workshops, role-playing games such as focus groups. The principles of activity, research (creative) position, objectivity (awareness) of behavior and partner (subject – subject) communication are considered in detail.
Keywords: тренинг; проектное обучение; мотив; знания; навыки; журналистика; project training; training; умения; практикум; студенческая аудитория; учебный курс; принцип активности; принцип исследовательской позиции; принцип объективности поведения; принцип партнерского общения; journalism; motive; knowledge; skills; workshop; student audience; training course; principles of activity; principles of research position; principles of objectivity of behavior; principles of partner communications